Longitudinal 3T MRI T2* mapping of Juvenile osteochondritis dissecans (JOCD) lesions differentiates operative from non‐operative patients—Pilot study. Issue 1 (30th April 2022) - Kajabi, Abdul Wahed; Zbýň, Štefan; Johnson, Casey P.; Tompkins, Marc A.; Nelson, Bradley J.; Takahashi, Takashi; Shea, Kevin G.; Marette, Shelly; Carlson, Cathy S.; Ellermann, Jutta M.
Abstract: Juvenile osteochondritis dissecans (JOCD) is an orthopedic joint disorder of children and adolescents that can lead to premature osteoarthritis. Thirteen patients (mean age: 12.3 years, 4 females), 15 JOCD‐affected and five contralateral healthy knees, that had a baseline and a follow‐up magnetic resonance imaging (MRI) (mean interval of 8.9 months) and were treated nonoperatively during this interval were included. Retrospectively, patients were assigned to operative or nonoperative groups based on their electronic medical records. Volumetric mean T 2 * values were calculated within regions of interest (progeny lesion, interface, parent bone) and region matched control bone in healthy contralateral knees and condyles. The normalized percentage difference of T 2 * between baseline and follow up MRI in nonoperative patients significantly increased in progeny lesion (−47.8%, p  < 0.001), parent bone (−13.9%, p  < 0.001), and interface (−32.3%, p  = 0.011), whereas the differences in operative patients were nonsignificant and below 11%. In nonoperative patients, the progeny lesion ( p  < 0.001) and interface T 2 * values ( p  = 0.012) were significantly higher than control bone T 2 * at baseline, but not at follow‐up ( p  = 0.219, p  = 1.000, respectively). In operative patients, the progeny lesion and interface T 2 * values remained significantly elevated compared to the control bone both at baseline ( p  < 0.001, p  < 0.001) and follow‐up ( p  < 0.001, p  < 0.001), respectively. Clinical Significance: Longitudinal T 2 * mapping differentiated nonhealing from healing JOCD lesions following initial nonoperative treatment, which may assist in prognosis and improve the ability of surgeons to make recommendations regarding operative versus nonoperative treatment.